STUDY ON CAVITATION PHENOMENA IN CENTRIFUGAL PUMPS USING VIBRATION SIGNAL AND TEMPERATURE PARAMETER - Ikhwansyah Isranuri; Mochamad Halley (Jurnal Dinamis, 2010)
ABSTRACTOne of failure in operation centrifugal pump is cavitation. Cavitation is one phenomenonappeared vapor bubbles cause net pressure in fluid is less than vapor pressure of fluid inoperation temperature of pump. Net Positive Suction Head (NPSH) used as safety parameter incavitation .NPSH divided in two kinds, Net Positive Suction Head Required (NPSHR) and NetPositive Suction Head Available (NPSHA). Cavitation occurs when NPSHA drops blow NPSHRfor a centrifugal pump. This study implemented with experiment and analysis about change ofcharacteristic cavitation in centrifugal pump cause variation NPSHA, change of temperature andincrease vibration signal with measuring in centrifugal pump housing. Experiment method usingin this research divided in two steps (direct and indirect experiment).Data from result of theexperiment will developed with statistic method to understand effect from variation NPSHA,vibration signal and increase fluid temperature, concerning cavitation phenomenon with statisticprocessing by MS-Excel and analyzing agree with vibration and temperature behavior. Forvibration signal occurs increase displacement amplitude each 1,80.10-6 m, 2,24.10-6 m and2,46. 10-6 m. Increase velocity amplitude each 1,38.10-5m/s, 1,66.10-5 and 1,97.10-5m/s. Andincrease acceleration amplitude each 1,038.10-4 m/s2, 1,028.10-4 m/s2 and 1,611.10-4 m/s2.Formeasuring fluid temperature in housing pump, for operation condition in 5 hour occurs increasefluid temperature each 0,010 oC,0,032 oC and 0,104 oC. Result of this research describe occursincrease vibration signal and fluid temperature in pump housing cause variation NPSHA.Keywords: Centrifugal Pump, Cavitation, NPSH,Vibration Signal, Temperature parameter